Occupational exposure to magnetic fields in relation to mortality from brain cancer among electricity generation and transmission workers. Issue 1 (January 1997) - Harrington, J M; McBride, D I; Sorahan, T; Paddle, G M; van Tongeren, M
Abstract : OBJECTIVE: To investigate whether the risks of mortality from brain cancer are related to occupational exposure to magnetic fields. METHODS: A total of 112 cases of primary brain cancer (1972-91) were identified from a cohort of 84, 018 male and female employees of the (then) Central Electricity Generating Board and its privatised successor companies. Individual cumulative occupational exposures to magnetic fields were estimated by linking available computerised job history data with magnetic field measurements collected over 675 person-workshifts. Estimated exposure histories of the case workers were compared with those of 654 control workers drawn from the cohort (nested case-control study), by means of conditional logistic regression. RESULTS: For exposure assessments based on arithmetic means, the risk of mortality from brain cancer for subjects with an estimated cumulative exposure to magnetic fields of 5.4-13.4 microT.y v subjects with lower exposures (0.0-5.3 microT.y) was 1.04 (95% confidence interval (95% CI) 0.60 to 1.80). The corresponding relative risk in subjects with higher exposures (> or = 13.5 microT.y) was 0.95 (95% CI 0.54 to 1.69). There was no indication of a positive trend for cumulative exposure and risk of mortality from brain cancer either when the analysis used exposure assessments based on geometric means or when the analysis was restricted to exposures received within five years of the case diagnosis (or corresponding period for controls). CONCLUSIONS: Although the exposure categorisation was based solely on recent observations, the study findings do not support the hypothesis that the risk of brain cancer is associated with occupational exposure to magnetic fields.